2022
DOI: 10.1186/s12886-022-02539-z
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors and associated factors among patients visiting BoruMeda Hospital’s secondary eye Unit in Dessie Town, South Wollo Zone, Ethiopia

Abstract: Background In Ethiopia, refractive error is the second leading cause of vision impairment and the third main cause of blindness. Because refraction services are scarce and difficult to obtain, many people with refractive error live with impaired vision or blindness for the rest of their lives. Objective The primary goal of this study was to determine the prevalence of refractive errors and associated factors among patients who visited Boru Meda Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
(12 reference statements)
2
3
2
Order By: Relevance
“… 25 , 28 But the finding of this study is higher than the study done in Addis Ababa and Borumeda hospital, South Wollo which is 4% and 18.34%, respectively. 15 , 17 The discrepancy seen between the above result and the current study might be due to research methodology differences and cut-off points for defining the outcome of interest that is in a study done in Nigeria, the PVA 6/9 or worse was considered as visual impairment. This hospital-based study is also higher than several other community-based studies in Ethiopia, which have shown rates ranging from 4% to 12.9%.…”
Section: Discussioncontrasting
confidence: 58%
“… 25 , 28 But the finding of this study is higher than the study done in Addis Ababa and Borumeda hospital, South Wollo which is 4% and 18.34%, respectively. 15 , 17 The discrepancy seen between the above result and the current study might be due to research methodology differences and cut-off points for defining the outcome of interest that is in a study done in Nigeria, the PVA 6/9 or worse was considered as visual impairment. This hospital-based study is also higher than several other community-based studies in Ethiopia, which have shown rates ranging from 4% to 12.9%.…”
Section: Discussioncontrasting
confidence: 58%
“…Budenz et al 36 , reported a reduction in visual impairment from 17.1% to 6.7% after refraction and correction with spectacle in a population-based study in Ghana. Consistent with the current findings, other hospital-based studies have reported higher prevalence of visual impairment in females than in males 24 , 25 . Studies suggest that the biological effects of female hormones, and socioeconomic factors could affect the uptake of eye care services 37 , 38 .…”
Section: Discussionsupporting
confidence: 93%
“…The odds of having RE among participants who had a history of diabetes mellitus were 4.02 times higher compared to participants who had no diabetes mellitus. This result is comparable with the studies conducted in Borumed, Ethiopia, and Yunnan, China [ 7 , 39 ]. Clinical research has demonstrated that transient RE shifts are related to blood glucose levels.…”
Section: Discussionsupporting
confidence: 90%
“…In Sub-Saharan Africa, the prevalence of RE was approximately 46% [ 5 , 6 ]. Hospital-based studies conducted in Gondar, Borumeda, and Arba Minch, Ethiopia showed that the prevalence of RE was 76.3%, 18.3%, and 27.5% respectively [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%